2009
DOI: 10.1097/gme.0b013e318184762e
|View full text |Cite
|
Sign up to set email alerts
|

Autogenic training to manage symptomology in women with chest pain and normal coronary arteries

Abstract: An 8-week AT program improves symptom frequency, with near-significant improvements in symptom severity in women with cardiac syndrome X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…152 Cognitive behavioural therapy can be offered as an adjunctive antianginal treatment, and has been shown to reduce the frequency and severity of symptoms in patients with signs and symptoms of ischaemia and no obstructive CAD during an 8-week period of autogenic training (a relaxation technique). 153,154 Conclusions CMD seems to have an important role in the adverse prognosis of both women and men with ischaemic heart disease and no obstructive CAD. Noninvasive cardio vascular MRI is an emerging modality that seems to have a higher sensitivity and specificity for detection of CMD than traditional imaging stress tests such as echocardiography and nuclear perfusion imaging.…”
Section: Reviewsmentioning
confidence: 99%
“…152 Cognitive behavioural therapy can be offered as an adjunctive antianginal treatment, and has been shown to reduce the frequency and severity of symptoms in patients with signs and symptoms of ischaemia and no obstructive CAD during an 8-week period of autogenic training (a relaxation technique). 153,154 Conclusions CMD seems to have an important role in the adverse prognosis of both women and men with ischaemic heart disease and no obstructive CAD. Noninvasive cardio vascular MRI is an emerging modality that seems to have a higher sensitivity and specificity for detection of CMD than traditional imaging stress tests such as echocardiography and nuclear perfusion imaging.…”
Section: Reviewsmentioning
confidence: 99%
“…123 Cognitive behavioral therapy has been shown to reduce symptoms severity and frequency. 124 Cardiac rehabilitation involves multiple sessions of cardiovascular exercise, psychological counseling and nutritional planning and can be helpful as it improves blood pressure, body mass index and exercise capacity. 125 …”
Section: Treatmentmentioning
confidence: 99%
“…Disease severity and progression have been shown to be related to a lack of support in women 34 , with increased psychosocial risk factors related to the degree of social isolation 35 . Previous studies among women with cardiac syndrome X have shown that behavioral treatments employed in a group environment have long-term beneficial effects on symptom severity 16 and psychological morbidity 15 , and, accordingly, this study has demonstrated the positive impact of group support among this patient population. Support group attendance reduced the noted decline in social support, while maintaining quality of life.…”
Section: Discussionmentioning
confidence: 81%
“…Behavioral interventions administered in a group format have successfully modified symptom severity and frequency among cardiac syndrome X patients 15,16 , suggesting that reducing social isolation may have a positive impact on the psychosocial health and quality of life in patients with cardiac syndrome X. Group support has been successfully applied to the treatment of coronary heart disease (CHD) 17 , breast cancer 18 and chronic pain 19 .…”
Section: Introductionmentioning
confidence: 99%